An Analysis of Deixis in The “Elemental” Movie - Zelkasih, Renda; Suadi, Suadi; Pratiwi, Resdilla (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2025)
This research aims to analyze the types and the factor influence of deixis found in the Elemental movie. The study applies Levinson’s theory of deixis, which classifies deixis into five categories: person, time, place (location), discourse, and social deixis. This research employs a qualitative descriptive method. The data are collected from the movie script of Elemental Movie (2023), focusing only on the characters’ spoken dialogues. Each deictic expression found in the script was identified, categorized, and analyzed based on Levinson’s Theory. The first findings show that a total of 320 deixis were found in the movie, consisting of 191 person deixis, 37 time deixis, 45 place deixis, 26 discourse deixis, and 21 social deixis. Person deixis is the most dominant, indicating that personal relationships and speaker-hearer references play a central role in the film. Second findings, the study identifies several contextual factors that influence deixis usage, including participant roles, usage function, levels of intimacy, formality/informality, and social status. These factors contribute to how deixis is used to reflect dynamics, emotional expressions, and narrative flow within movie.